Global predictions for astrophysics applications - Demetriou, P. (HNPS Advances in Nuclear Physics, 2020)
Nuclear reaction rates play a crucial role in nuclear astrophysics. In the last decades there has been an enormous effort to measure reaction cross sections and extensive experimental databases have been compiled as a result. In spite of these efforts, most nuclear reaction network calculations still have to rely on theoretical predic- tions of experimentally unknown rates. In particular, in astrophysics applications such as the s-, r- and p-process nucleosynthesis involving a large number of nuclei and nuclear reactions (thousands). Moreover, most of the ingredients of the cal- culations of reaction rates have to be extrapolated to energy and/or mass regions that cannot be explored experimentally. For this reason it is important to develop global microscopic or semi-microscopic models of nuclear properties that give an accurate description of existing data and are reliable for predictions far away from the stability line. The need for more microscopic input parameters has led to new devel- opments within the Hartree-Fock-Bogoliubov method, some of which are presented in this paper.